Incidence of and Predictors for Early Discontinuation of Biological Therapies in Veteran Patients with Inflammatory Bowel Disease. Issue 8 (August 2017) - Feagins, Linda A.; Waljee, Akbar; Hou, Jason K.; Gu, Phillip; Kanjo, Steven; Rudrapatna, Vivek; Cipher, Daisha J.; Govani, Shail; Gaidos, Jill
Abstract : Background: Biological therapies are effective for inducing and maintaining remission in inflammatory bowel disease (IBD), but patients often require changes in biological agents over the course of their illness. We sought to evaluate the rate of and reasons for discontinuing biological agents and to identify risk factors for their discontinuation. Methods: We performed a retrospective cohort study across 4 VA hospital systems (Dallas, TX; Houston, TX; Ann Arbor, MI; Richmond, VA). Patients with IBD who were started on biological therapy between 1998 and 2015 were identified, and their medical records were reviewed to confirm the diagnosis of IBD and to collect study data. Results: Of 1969 patients with IBD; 256 were treated with 346 courses of therapy. By 6 months after initiation of therapy, 82 (24%) had stopped the biological agent. Among patients starting their first biological agent, 21.5% had stopped by 6 months. Patients taking a concomitant thiopurine and those with ileocolonic disease or a nonpenetrating, nonstricturing phenotype were less likely to discontinue biological therapy, whereas those taking 5-ASA concomitantly were more likely to discontinue biological therapy. The most common reasons for discontinuation were primary nonresponse (40%) and adverse drug reactions (29%). Conclusions: In conclusion, in a large multicenter VA cohort, we found that 24% of patients who are prescribed a biological stop their treatment early, most commonly for primary nonresponse or for an adverse drug reaction. Consideration should be given to treating patients with a concomitant thiopurine if at all possible, as this reduces the likelihood of early discontinuation. Abstract : Article first published online 24 May 2017.